Interferência de Calotropis procera nas culturas de milho e feijão caupi e seu controle químico - Sarmento, Hercules Gustavo dos Santos (2019)
The Calotropis procera (Ailton) shrub popularly known as silk cotton, has great affinity for desert and arid regions and sandy soils. They occur in plantations, degraded pastures, on the seaside, dunes, vacant lots and roadsides, tolerate poor soils, acid soils, saline. Calotropis procera is an exotic plant, and weed plants are highly efficient in competition for resources and can cause serious environmental and economic damage, thus, the study of weeds becomes strategic to delineate integrated species management programs. The objective of this work was to evaluate the effect of competition of C. procera on maize and cowpea crops as well as their germination in abiotic stresses and to select herbicides for their control. The experiments were conducted at the Federal University of Ceará (UFC). In the first competition experiment, the characteristics associated to water use - transpiratory rate, stomatal conductance, water use efficiency, as well as photosynthesis, internal CO2 concentration in the leaf, average leaf temperature at the time of evaluation and photosynthetic rate. In the second, the water stress (PEG 600) and saline (NaCl) were simulated, evaluating the germination and seed vigor. In the last experiment, different herbicides were applied to the control of C. procera, evaluating the rate of electron transport, phytotoxicity and regrowth of weed. According to the results the photosynthetic, transpiratory and stomatal conductance rates were negatively influenced in the corn and bean crop by competition with C. procera and the competition level of 16 plants per pot was the one that most negatively affected the aerial part dry matter and growth rate of the crop. The water and saline stress conditions reduced the physiological quality of the seeds and the damages caused by the reduction of the water potential were more accentuated in relation to the saline stress and the different temperatures influenced the physiological parameters evaluated, obtaining the best results within the temperature range of 26.7 to 29.9 °C. All herbicides were efficient for the control of C. procera in the development stages 30 DAP and when applied in regrowth of plants with 150 DAP. The herbicide tembotrione has a reduced and slower effect when compared to the other herbicides in the control of C. procera.